The interaction between stress and metabolic disruption in studentpopulation – preliminary study - Rog, Joanna; Rząd, Zuzanna; Karakuła-Juchnowicz, Hanna (Current Problems of Psychiatry, 2021)
Introduction. Approximately 26% of individuals between 18 and 24 years old are overweight or obese, and the number of persons with excessive body mass index (BMI) is growing. Obesity increases the risk of metabolic disruptions, which is well connected with mental health problems. Stressful situations, including entering adulthood and starting university education, affect food choices negatively. The aim of the study was to examine the relationship between psychological stress and body composition in the student population. Materials and methods. The study group consisted of 80 students (76% of women and 24% of men) between 19 and 28 years old from universities in Lublin. To determine anthropometric measurement (fat-free mass (FFM), fat mass (FM), total body water (TBW), intracellular (ICF) and extracellular (ECF) fluids), bioelectrical impedance analysis (BIA) method was applied. The severity of stress symptoms was measured using Perceived Stress Scale (PSS-10). Results. When it comes to 41.25% of participants, they used relaxation techniques, mainly meditation, yoga practice and walking. Most students had optimal body weight. While 60% of individuals had high stress levels. The perceived stress was not related to using the relaxation methods. Individuals with the high stress severity were characterized by lower: TBW, ECF and ICF expressed in liters, and lower FFM represented in kilograms. The inverse relationship between the severity of stress and the aforementioned parameters was also detected (p<0.05). Conclusions. Implementing appropriate health education programs to prevent negative changes in anthropometric measurements, psychological stress, and their health-related consequences in the student population should be considered.